ENGLISH VERSIONS OF UZBEK PAREMIES AND THEIR SPECIFIC FEATURES - SULAYMONOVA D.X (International Journal of Innovations in Engineering Research and Technology, 2021)
this article analyzes the importance and advantages of essays in teaching English in a specialty, teaching speaking skills, and is important for the student’s language learning. This article also discusses the educational value of articles and the benefits of using them. Russian and English translations of articles on a specific topic in Uzbek are given and analyzed. The use of these proverbs serves to shape the spirituality of the youth.